Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1525-1446.2007.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Credentialing for Public Health Nurses: Personally Valued … But Not Well Recognized

Abstract: These findings provide guidance to public health nursing leaders and inform discussions regarding the development of credentialing systems within the field of public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 24 publications
0
26
1
Order By: Relevance
“…Certified nurses with other specialty certifications who were evaluated in this study included those having medical/surgical, oncology, and geriatrics certifications. 57 Results of another study showed that nurses who were certified in oncology obtained higher scores on the Nurses' Knowledge and Attitude Survey Regarding Pain. Ratings were inconsistent, however, among the staff and supervisory nurses; only the latter group reported differences between certified and noncertified nurses.…”
Section: Nurse Competence and Validation Of Knowledgementioning
confidence: 99%
See 2 more Smart Citations
“…Certified nurses with other specialty certifications who were evaluated in this study included those having medical/surgical, oncology, and geriatrics certifications. 57 Results of another study showed that nurses who were certified in oncology obtained higher scores on the Nurses' Knowledge and Attitude Survey Regarding Pain. Ratings were inconsistent, however, among the staff and supervisory nurses; only the latter group reported differences between certified and noncertified nurses.…”
Section: Nurse Competence and Validation Of Knowledgementioning
confidence: 99%
“…1,7,11,40,[54][55][56] In a survey of more than 11 000 nurses conducted by the ABNS, more than 90% of nurses who were surveyed concurred that certification validated knowledge in their specialty and indicated clinical competence. 11,25,33,34,40,41,53,[57][58][59] In one study, a relationship between certification and knowledge was reported. 11,25,33,34,40,41,53,[57][58][59] In one study, a relationship between certification and knowledge was reported.…”
Section: Nurse Competence and Validation Of Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“… increased patient confidence in nursing care; greater respect and recognition from the employer, nursing peers, and other health care professionals; the ability to expand professional responsibilities; greater earning potential and professional advancement opportunities; reimbursement for the certification examination; and increased collaborative practice …”
Section: Personal and Professional Rewardsmentioning
confidence: 99%
“…Reviews of more than 90 years of effort to measure, describe, and improve public health practice and systems performance (82,94) show that many of the same basic challenges for measuring systems performance persist. In addition, new and re-emphasized priorities in public health practice, such as voluntary agency accreditation (46,58,72,91), workforce credentialing (12,16,23,68), quality improvement (74,75,85), and service value measurement (36,43,66), will increase expectations for PHSR science to integrate and understand effects of these efforts at multiple systems levels.…”
Section: Conclusion and Future Issuesmentioning
confidence: 99%